Pengembangan Paket Pembelajaran Kimia Berbantuan Powerpoint Pada Materi Struktur Atom - Rini Yasinta Sasuang; Abdon Saiya (Oxygenius Journal Of Chemistry Education, 2022)
This study uses the Research and Development (R&D) method. The purpose of this research is to develop and determine the quality of powerpoint-assisted learning media. The research subjects were students of class X MIA 3 at SMA Catholic Don Bosco Bitung. The validation test of the four learning media assessment teams obtained 78.5% results, the material assessment team's validation test obtained 79.8% results. The overall results from the validation of the media assessment team and the material assessment team obtained an average result of 79.2% in the valid assessment category. The results of the teacher's response obtained a total score of 44 with an average of 88% included in the very interested category. The results of the first trial of 5 students obtained an average percentage of 36% of students who answered Strongly Agree, 52% of students who answered Agree, 10% of students who answered Disagree, 2% of students who answered Disagree, and 0% Strongly Do not agree. The results of the second trial of 10 students after repairs were made, the average percentage obtained was 67% of students who answered Strongly Agree, 33% of students who answered Agree. Based on the results of the responses of the two groups, it can be concluded that there was an increase in the large group